New Pharmacogenetic Markers to Predict the Risk of Bleeding During Taking of Direct Oral Anticoagulants - K. B. Mirzaev; D. V. Ivashchenko; I. V. Volodin; E. A. Grishina; K. A. Akmalova; A. A. Kachanova; A. I. Skripka; R. M. Minnigulov; T. E. Morozova; O. A. Baturina; A. N. Levanov; T. V. Shelekhova; et al. (Столичная издательская компания, 2020)
Aim. To search for new pharmacogenetic biomarkers of bleeding risk in patients taking rivaroxaban and dabigatran for different indications: atrial fibrillation, endoprosthesis of large joints of lower limbs.Material and methods. The study enrolled 29 patients (17 patients received dabigatran and 12 -rivaroxaban), who had hemorrhagic complications during taking direct oral anticoagulants. To find new pharmacogenetic biomarkers of bleeding risk, a next generation sequencing (NGS) was performed for selected candidate genes.Results. Among the patients with bleeding who received dabigatran, 13 variants of the nucleotide sequence showed statistically significant deviation from the population values: 11 in the CES1 gene and 2 in the ABCB1 gene. Among the patients with bleeding who received rivaroxaban, 7 variants of nucleotide sequence showed significant deviation: 4 in the ABCG2 gene, 2 in the CYP3A4 gene, and 1 in the ABCB1 gene.Conclusion. The identified in this study polymorphisms of candidate genes ABCB1, ABCG2, CES1, CYP3A4 were associated with the risk of bleeding in patients taking rivaroxaban and dabigatran. It makes an important contribution to the pharmacogenetics of direct oral anticoagulants and require additional assessment of clinical significance in further studies.